Bioavailability of elements in atmospheric PM2.5 during winter episodes at Central Eastern European urban background site. (15th January 2021) - Juda-Rezler, Katarzyna; Zajusz-Zubek, Elwira; Reizer, Magdalena; Maciejewska, Katarzyna; Kurek, Eliza; Bulska, Ewa; Klejnowski, Krzysztof
Abstract: The analysis of bioavailability and potential risk to human health of trace and minor elements bound to atmospheric PM2.5 was carried out at an urban background site in Warsaw, Poland during a 40-day winter period. The samples were sequentially extracted into four different fractions: water soluble (F1), reducible (F2), oxidizable (F3) and residual (F4) for the chemical fractionation of 8 elements: As, Cd, K, Mn, Pb, Sb, Ti and Zn, and further analyzed using inductively coupled plasma mass spectrometry in each fraction. The average PM2.5 mass concentration of 31.81 μg/m 3 (±19.73 μg/m 3 ) was exceeding daily WHO air quality guideline, while concentrations rose up to 50–70 μg/m 3 during episode days. Total concentrations of all analyzed elements were higher during the episode periods, with the highest increases for K, Pb (2 times) and Cd (1.7 times). All elements exhibited high bioavailability, as well as very high (K, Ti, Zn) and high (As, Cd, Mn, Pb, Sb) risk assessment code, with both features rising in episodic days up to 20% and more than 60%, respectively. Cancer risk for adults resulted from inhalation exposure to the most bioavailable fractions (F1 and F2) of human carcinogen As. It was higher than the precautionary criterion (1 · 10 −6 ) and increased during the days with elevated PM2.5 levels. Graphical abstract: Image 1 Highlights: Daily winter PM2.5 levels at Central European urban site are well above WHO AQG. Concentrations of trace elements (TEs) rise during episodes. The most bioavailable fraction (F1) constitutes more than 50% of TEs concentration. Bioavailability index rises during episodes for majority of TEs. Concentrations of As might pose carcinogenic risk to urban population.